The modified GTN-Thomason criterion for modelling of ductile fracture considering shear factor and size effect in micro-scaled plastic deformation. (15th August 2021) - Li, W.T.; Cai, Z.Y.; Li, H.; Peng, L.F.; Lai, X.M.; Fu, M.W.
Highlights: The GTN-Thomason model is modified by considering shear factor and size effect. The modified model is validated using different stress states and grain sizes. Decrease of the normalized third invariant ξ accelerates void shear and growth. Finer grains cause faster void nucleation, shear and growth to fracture in low ξ. Coarser grains help the start of void coalescence and growth to fracture in high ξ. Abstract: Coarser grains lead to fewer voids on the fracture surfaces of miniaturized workpiece via affecting the void nucleation, while finer grains result in a higher flow strength by influencing void growth. Furthermore, finer grains make the occurrence of normal tensile fracture difficult, but they accelerate the happening of shear-dominated fracture. These insights help the development of ductile fracture criterion by considering the fracture micro-mechanism in micro-scaled plastic deformation. Shear factor and size effect are thus introduced into the newly modified GTN-Thomason criterion to predict the ductile fracture in micro-scaled plastic deformation of copper sheets with different microstructural grain sizes and deformation stress states. The developed criterion is implemented in simulation of deformation process and well validated to be efficient by corroboration of the experimental results and the simulated load-stroke responses and deformation profiles of five sheets with different grain sizes and stress states. According to the accurate simulation results, the influences of stress triaxiality, the normalized third invariant and grain size on void evolution are further analysed. The results show that the increase of the normalized invariant prevents void shear and leads to a better ductility, while the increase of stress triaxiality facilitates the growth of voids to result in a worse ductility. When the deformation with a relatively high normalized invariant has an ignored void shear, the increase of grain size accelerates the onset of void coalescence and the rate of void growth, leading to a rapid failure. However, when the deformation with a relatively low normalized invariant has an unneglected void shear, finer grains increases the rates of void nucleation, growth and shear, causing a smaller fracture strain. These findings and the modified GTN ductile fracture criterion enhance the understanding and prediction of ductile fracture in micro-scaled plastic deformation, respectively, and further facilitate the development of microparts using by deformation-based micro-manufacturing process. Graphical abstract: Image, graphical abstract